Production of recombinant Human T Lymphotropic Virus type 1 Tax protein in Rosetta (DE3) bacterial host - Saffar, Samaneh; Azadmanesh, Keyhan; Golmohammadi, Taghi; Golkar, Majid; Amminian, Mahdi; Mirshahabi, Hesam; Rafatpanah, Hooshang (Archives of Advances in Biosciences, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> HTLV1 is the first detected retrovirus causing disease in human. The physiopathology of HTLV1 related diseases was mainly linked with its Tax protein characteristics. Use of mutant Tax proteins accompanied by immune regulator drugs could help treating HTLV1 associated myelopathy patients as a modulator of potent immune response against this viral protein. Since Tax protein is not commercially available, production of recombinant Tax protein was targeted for this study. Coding sequence of Tax protein (containing R222K mutation) in the pcDNA3.1(+) was digested with BamHI and XhoI restriction enzymes, and then removed and inserted into the expression vector pET32a(+) within the same cutting sites and cloned into E.coli DH5α. Recombinant vector was confirmed with enzymatic digestion, colony PCR, and sequencing of cloned gene. E.coli Rosetta (DE3) was transformed with the recombinant plasmid and the expression was induced. The expression of protein was assayed with SDS-PAGE and western blot using monoclonal antibodies against Tax and 5His epitope. Finally, antigenic characteristic of the recombinant protein was evaluated by western blotting against patient sera. Presence of Tax protein band in the SDS-PAGE and western blot was confirmed. Western blotting of the recombinant protein with patient sera showed the band related to Tax protein. The recombinant protein is well produced and could be detected by patients’ sera, making it eligible to be used as a recombinant viral antigen for future purposes.